Flue gas inhibitor, preparation method thereof and application of flue gas inhibitor in asphalt

By pickling and calcining, and introducing iron ions, the flue gas inhibitor with multiple adsorption mechanism is solved, and the problems of poor flue gas inhibition effect and complex process in the prior art are solved, and efficient flue gas suppression and the improvement of asphalt performance are achieved.

CN119735860APending Publication Date: 2025-04-01CHONGQING JIAOTONG UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411684215.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When existing flue gas inhibitors are used in asphalt, the flue gas inhibition effect is poor, the process is complicated and difficult to be suitable for large-scale production.

Method used

The eloite nanotubes are treated by pickling and calcining, impurities on their surface and cavity are removed, and iron ions are introduced to form a flue gas inhibitor with a multiple adsorption mechanism.

Benefits of technology

The smoke adsorption effect of flue gas inhibitors is significantly improved, with the smoke inhibition rate of 32% to 39%, and the gas inhibition rate of 70% to 75%, and meets the requirements of high temperature stability, low temperature crack resistance and water stability in the "Technical Specifications for Construction of Highway Asphalt Pavements".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005149047970000091
    Figure BDA0005149047970000091
  • Figure BDA0005149047970000101
    Figure BDA0005149047970000101
  • Figure BDA0005149047970000111
    Figure BDA0005149047970000111
Patent Text Reader

Abstract

The invention relates to a flue gas inhibitor as well as a preparation method and application thereof in asphalt, and the method comprises the following steps: firstly, pickling, washing and roasting a halloysite nanotube, then introducing iron ions into an inner cavity of the halloysite nanotube, and then preparing the flue gas inhibitor through interface modification. The invention further relates to application of the smoke inhibitor in asphalt. The smoke-inhibiting asphalt is prepared by mixing the prepared smoke inhibitor and heated asphalt according to a certain proportion. According to the method, the halloysite nanotube has a large specific surface area and a large pore structure, the adsorption performance of the halloysite nanotube is enhanced, and combination of iron ions and halloysite can adsorb and capture some volatile organic compounds and flue gas particles generated in the combustion process; through multiple mechanisms of chemical catalysis, thermal stability enhancement, free radical capture, physical adsorption and the like, the smoke suppression effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road construction materials, in particular to a smoke inhibitor and a preparation method thereof and application thereof in asphalt. Background Art

[0002] Asphalt is an organic cementitious material that is waterproof, moisture-proof and anti-corrosive. It is used in industrial and construction pavements such as coatings, plastics and rubber. During use, especially under high temperature conditions during pavement construction, the hydrocarbons and their derivatives in the asphalt material undergo oxidation reactions to produce a large amount of volatile substances, namely asphalt fume. Asphalt fume is a special pollutant that not only pollutes the environment but also harms human health.

[0003] At present, one of the main measures to reduce asphalt fume emissions is to add admixtures to asphalt materials, which can be roughly divided into three categories: inhibitors, warm mix agents and flame retardants. The respective emission reduction effects are 50% to 70%, 40% to 50% and 10% to 40%, respectively. In comparison, the most direct and effective way to achieve asphalt fume emission reduction is to add inhibitors.

[0004] Chinese patent CN 118085595 B discloses a smokeless soluble rubber powder composite modified asphalt and its preparation method, wherein the modification method of halloysite nanotubes is to mix halloysite nanotubes, octadecyl trimethyl ammonium chloride, dodecyl phosphate, and anhydrous ethanol in a certain mass ratio, heat to 70-90°C, control the stirring rate at 400-650 rpm, condense and reflux for 3-7 hours, filter and separate, and dry the obtained solid at 75-90°C for 1-2 hours to obtain modified halloysite nanotubes. However, the modification method of halloysite nanotubes involved in the above patent does not perform surface impurity removal and internal cavity expansion treatment on the halloysite nanotubes, resulting in the smoke adsorption effect not reaching the best effect; and the process is relatively complicated and difficult to be applied to large-scale production and application of the project.

[0005] It can be seen from this that the current research and development of smoke suppressants is not in-depth enough, and there are shortcomings such as poor smoke suppression effect, poor compatibility and reduced asphalt road performance. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a smoke suppressant and a preparation method thereof and application thereof in asphalt.

[0007] The technical solution of the present invention is:

[0008] A method for preparing a smoke suppressant comprises the following steps:

[0009] 1) Weigh the components by weight: 10-50 parts of halloysite nanotubes, 25-125 parts of acid solution, 0.1-2.5 parts of anhydrous ferric chloride, 500-600 parts of deionized water, 500-600 parts of ethanol, 0.3-1.5 parts of silane coupling agent, and 0.3-1.5 parts of stearic acid;

[0010] 2) washing the halloysite nanotubes with acid and then washing with water until they are neutral;

[0011] 3) drying, grinding and calcining the washed halloysite nanotubes to obtain intermediate A;

[0012] 4) Dissolving intermediate A in an ethanol solution, mixing with anhydrous ferric chloride, and drying to obtain intermediate B;

[0013] 5) mixing a silane coupling agent and stearic acid to obtain an intermediate C;

[0014] 6) Intermediate B and intermediate C are mixed, condensed and refluxed, and then dried to obtain solution D;

[0015] 7) The solution D is centrifuged and dried to obtain a smoke suppressant.

[0016] Furthermore, the silane coupling agent in step 1) is an aminosilane coupling agent.

[0017] Furthermore, the acid solution in step 1) is dilute sulfuric acid or dilute acetic acid.

[0018] Furthermore, the concentration of the acid solution in step 1) is 30-40%.

[0019] Furthermore, the index of the halloysite nanotubes in step 1) is 30-50 nm, and the specific surface area is 30-70 m 2 / g, length 100~500nm, mesh number 1250~2000mesh.

[0020] Furthermore, the acid washing method in step 2) is to mix the halloysite nanotubes with the acid solution and react in a water bath at 75-85° C. for 1.5-2.5 hours.

[0021] Furthermore, the drying condition in step 3) is drying at 75-85° C. for 5-7 hours, and the calcination condition is calcining at 400° C.-500° C. for 3-5 hours.

[0022] Furthermore, the centrifugation condition in step 7) is centrifugation at a rotation speed of 12000-14000 rpm for 5-10 min, and the drying condition is drying at 120-180° C. for 10-15 h.

[0023] The smoke suppressant is prepared according to the above method.

[0024] A smoke suppressant asphalt containing the above-mentioned smoke suppressant is obtained by uniformly mixing the smoke suppressant with heated asphalt, wherein the smoke suppressant accounts for 1% to 5% of the mass of the asphalt.

[0025] The smoke suppression mechanism of the smoke suppressant prepared according to the method of the present invention is as follows.

[0026] ① Formation of π-complex

[0027] Iron ions can interact with the π electron clouds in aromatic hydrocarbon compounds to form π complexes. This process usually involves electronic interactions between the π electrons on the aromatic ring and the d orbitals of the iron ions. For example, Fe 2+ or Fe 3+ It can form the following complex with benzene molecules:

[0028] Fe 2+ +C6H6→[Fe(η 6 -C6H6)] 2+

[0029] Among them, η 6 This means that all six carbon atoms of the benzene ring participate in the coordination with the iron ion. The formation of this complex is due to the electrostatic attraction between the positive charge of the iron ion and the π electron cloud of the aromatic ring.

[0030] ② Oxidation reaction of iron salts and aromatic hydrocarbons

[0031] Iron ions (especially Fe 3+ ) can undergo oxidation reactions with aromatic hydrocarbons, converting them into corresponding oxidation products. For example, in the presence of FeCl3, benzene can be oxidized to form chlorobenzene:

[0032] FeCl3+C6H6→FeCl2+C6H5ClHCl

[0033] In this reaction, Fe 3+ As an oxidant, it oxidizes benzene to chlorobenzene and is reduced to Fe 2+ .

[0034] ③ Formation of metal complexes

[0035] Iron ions can form complexes with heteroatoms (such as nitrogen, oxygen, sulfur, etc.) in aromatic compounds. For example, aromatic compounds containing nitrogen atoms (such as pyridine, pyrrole, etc.) can coordinate with iron ions to form stable complexes:

[0036] Fe 3+ +3C5H5N[Fe(C5H5N3] 3+

[0037] The nitrogen atom of pyridine (C5H5N3) provides a lone pair of electrons to react with Fe 3+ Coordination

[0038] ④Aromatization reaction catalyzed by iron ions

[0039] In organic synthesis, iron ions can be used as catalysts to promote aromatization reactions. Iron catalysts can promote the dehydrogenation of cycloalkanes to produce aromatic hydrocarbons. In such reactions, iron ions can reduce the activation energy of the reaction by forming transition state complexes.

[0040] ⑤ Physical adsorption

[0041] Halloysite nanotubes have a large specific surface area and pore structure, and the introduction of iron ions may enhance their adsorption performance. The combination of iron ions and halloysite can adsorb and capture some volatile organic compounds and flue gas particles produced during the combustion process, reducing their release into the external environment.

[0042] In summary, the introduction of iron ions into halloysite nanotubes can achieve smoke suppression effects through multiple mechanisms such as chemical catalysis, thermal stability enhancement, free radical capture, and physical adsorption. The combined effect of these mechanisms enables halloysite nanotubes to effectively reduce smoke generation during asphalt construction.

[0043] The beneficial effects of the present invention are as follows:

[0044] 1. The present invention relates to a smoke suppressant and a preparation method thereof and application in asphalt. The method of the present invention removes impurities in the inner cavity and outer surface of halloysite nanotubes by acid washing and roasting, thereby enhancing the smoke adsorption effect of the halloysite nanotubes.

[0045] 2. The smoke suppressant and preparation method thereof described in the present invention introduces iron ions into halloysite nanotubes after impurities are removed, and adsorbs and captures some volatile organic compounds and smoke particles generated during the combustion process through multiple mechanisms such as chemical catalysis, thermal stability enhancement, and free radical capture, thereby further enhancing the smoke adsorption effect of the halloysite nanotubes.

[0046] 3. The smoke suppressant and preparation method thereof described in the present invention, the halloysite nanotubes used have a large specific surface area and pore structure, which is an important basis for enhancing the smoke adsorption effect.

[0047] 4. The smoke suppressant prepared by the method of the present invention can also be used for asphalt. The applicant has experimentally verified that the high temperature stability, low temperature crack resistance and water stability of the prepared smoke suppressant asphalt meet the "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004), and at the same time has better smoke suppression effect and is suitable for large-scale application and production. DETAILED DESCRIPTION

[0048] The present invention is further described in detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technicians in this field can make some non-essential improvements and adjustments to the present invention based on the above application content.

[0049] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.

[0050] Sources:

[0051] In the following examples, the halloysite nanotubes used were purchased from Shijiazhuang Dinglei Mineral Products Trading Co., Ltd., with a technical index of 40 nm and a specific surface area of ​​50 m 2 / g, length 300nm, mesh size 1500 mesh.

[0052] Sulfuric acid solution was purchased from Chengdu Kelong Chemicals Co., Ltd.

[0053] Acetic acid solution was purchased from Chengdu Kelong Chemicals Co., Ltd.

[0054] The index of anhydrous ferric chloride is molecular weight 162.20g / mol and density 2.9g / cm 3 , specifically purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0055] Deionized water was prepared using the U-Pure series ultrapure water machine produced by Sichuan U-Pure Ultrapure Technology Co., Ltd.

[0056] The density of ethanol is 0.789 g / mL, and it was purchased from Chengdu Kelong Chemicals Co., Ltd.

[0057] The silane coupling agent KH550 has a molecular weight of 221.37 g / mol and a density of 0.946 g / ml, and is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0058] The molecular weight of stearic acid is 284.48 g / mol, the melting point is 68-71° C., and it is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0059] Example 1 Example 1 is a method for preparing a smoke suppressant

[0060] A method for preparing a smoke suppressant comprises the following steps:

[0061] ① Weigh the raw materials by weight, including 10 parts of halloysite nanotubes, 25 parts of 30% sulfuric acid, 500 parts of deionized water, 500 parts of ethanol solution, 0.1 parts of anhydrous ferric chloride solution, 0.3 parts of stearic acid, and 0.3 parts of KH550 silane coupling agent;

[0062] ② 10 parts of halloysite nanotubes and 25 parts of 30% sulfuric acid were reacted in a water bath at 80°C for 2 hours, fully stirred at a speed of 1000 rpm and then allowed to stand for 24 hours. After standing, the acid-leached halloysite nanotubes were washed with 500 parts of deionized water, the washing supernatant was filtered off, and the operation was repeated until neutral;

[0063] ③ Dry the washed halloysite nanotubes at 80°C for 6 hours and grind them into powder. Put the washed halloysite nanotubes into a muffle furnace and heat them at 450°C for 3 hours to dry them, finally obtaining the experimental intermediate A;

[0064] ④ Mix 500 parts of ethanol solution containing intermediate A with 0.1 parts of anhydrous ferric chloride solution, filter and vacuum dry to obtain experimental intermediate B;

[0065] ⑤ Stir and blend 0.3 parts of stearic acid and 0.3 parts of KH550 silane coupling agent to obtain experimental intermediate C;

[0066] ⑥ Mix and stir the experimental intermediate B and the experimental intermediate C in a water bath pot, set the temperature to 80°C, condense and reflux, and vacuum dry to obtain solution D;

[0067] ⑦ The solution D obtained in step ⑥ was centrifuged at 12000 rpm for 5 min. After centrifugation, it was dried at 150° C. for 12 h to finally obtain a smoke suppressant.

[0068] Example 2 This example is a method for preparing a smoke suppressant

[0069] A method for preparing a smoke suppressant comprises the following steps:

[0070] ① Weigh the raw materials by weight, including 30 parts of halloysite nanotubes, 75 parts of 30% sulfuric acid, 550 parts of deionized water, 550 parts of ethanol solution, 2.5 parts of anhydrous ferric chloride solution, 1.5 parts of stearic acid, and 1.5 parts of KH550 silane coupling agent;

[0071] ② 30 parts of halloysite nanotubes and 75 parts of 30% sulfuric acid were reacted in a water bath at 80°C for 2 hours, fully stirred at a speed of 1000 rpm and then allowed to stand for 24 hours. After standing, the acid-leached halloysite nanotubes were washed with 550 parts of deionized water, the washing supernatant was filtered off, and the operation was repeated until neutral;

[0072] ③ Dry the washed halloysite nanotubes at 80°C for 6 hours and grind them into powder. Put the washed halloysite nanotubes into a muffle furnace and heat them at 450°C for 3 hours to dry them, finally obtaining the experimental intermediate A;

[0073] ④ Mix 550 parts of ethanol solution containing intermediate A with 2.5 parts of anhydrous ferric chloride solution, filter and vacuum dry to obtain experimental intermediate B;

[0074] ⑤ Stir and blend 1.5 parts of stearic acid and 1.5 parts of KH550 silane coupling agent to obtain experimental intermediate C;

[0075] ⑥ Mix and stir the experimental intermediate B and the experimental intermediate C in a water bath pot, set the temperature to 80°C, condense and reflux, and vacuum dry to obtain solution D;

[0076] ⑦ The solution D obtained in step ⑥ was centrifuged at 12000 rpm for 5 min. After centrifugation, it was dried at 150° C. for 12 h to finally obtain a smoke suppressant.

[0077] Example 3 This example is a method for preparing a smoke suppressant

[0078] A method for preparing a smoke suppressant comprises the following steps:

[0079] ① Weigh the raw materials by weight, including 50 parts of halloysite nanotubes, 125 parts of 30% acetic acid, 600 parts of deionized water, 550 parts of ethanol solution, 0.1 parts of anhydrous ferric chloride solution, 0.3 parts of stearic acid, and 0.3 parts of KH550 silane coupling agent;

[0080] ② 50 parts of halloysite nanotubes and 125 parts of 30% acetic acid were reacted in a water bath at 80°C for 2 hours, fully stirred at a speed of 1000 rpm and then allowed to stand for 24 hours. After standing, the acid-leached halloysite nanotubes were washed with 600 parts of deionized water, the washing supernatant was filtered off, and the operation was repeated until neutral;

[0081] ③ Dry the washed halloysite nanotubes at 80°C for 6 hours and grind them into powder. Put the washed halloysite nanotubes into a muffle furnace and heat them at 450°C for 3 hours to dry them, finally obtaining the experimental intermediate A;

[0082] ④ Mix 550 parts of ethanol solution containing intermediate A with 0.1 parts of anhydrous ferric chloride solution, filter and vacuum dry to obtain experimental intermediate B;

[0083] ⑤ Stir and blend 0.3 parts of stearic acid and 0.3 parts of KH550 silane coupling agent to obtain experimental intermediate C;

[0084] ⑥ Mix and stir the experimental intermediate B and the experimental intermediate C in a water bath pot, set the temperature to 80°C, condense and reflux, and vacuum dry to obtain solution D;

[0085] ⑦ The solution D obtained in step ⑥ was centrifuged at 12000 rpm for 5 min. After centrifugation, it was dried at 150° C. for 12 h to finally obtain a smoke suppressant.

[0086] Example 4 This example is a method for preparing a smoke suppressant

[0087] A method for preparing a smoke suppressant comprises the following steps:

[0088] ① Weigh the raw materials by weight, including 50 parts of halloysite nanotubes, 125 parts of 30% acetic acid, 600 parts of deionized water, 550 parts of ethanol solution, 2.5 parts of anhydrous ferric chloride solution, 1.5 parts of stearic acid, and 1.5 parts of KH550 silane coupling agent;

[0089] ② 50 parts of halloysite nanotubes and 125 parts of 30% acetic acid were reacted in a water bath at 80°C for 2 hours, fully stirred at a speed of 1000 rpm and then allowed to stand for 24 hours. After standing, the acid-leached halloysite nanotubes were washed with 600 parts of deionized water, the washing supernatant was filtered off, and the operation was repeated until neutral;

[0090] ③ Dry the washed halloysite nanotubes at 80°C for 6 hours and grind them into powder. Put the washed halloysite nanotubes into a muffle furnace and heat them at 450°C for 3 hours to dry them, finally obtaining the experimental intermediate A;

[0091] ④ Mix 550 parts of ethanol solution containing intermediate A with 2.5 parts of anhydrous ferric chloride solution, filter and vacuum dry to obtain experimental intermediate B;

[0092] ⑤ Stir and blend 1.5 parts of stearic acid and 1.5 parts of KH550 silane coupling agent to obtain experimental intermediate C;

[0093] ⑥ Mix and stir the experimental intermediate B and the experimental intermediate C in a water bath pot, set the temperature to 80°C, condense and reflux, and vacuum dry to obtain solution D;

[0094] ⑦ The solution D obtained in step ⑥ was centrifuged at 12000 rpm for 5 min. After centrifugation, it was dried at 150° C. for 12 h to finally obtain a smoke suppressant.

[0095] Comparative Example 1

[0096] The preparation method of the smoke suppressant of this comparative example is basically the same as that of Example 3, except that only the inner cavity and the surface of the halloysite nanotubes are acid-washed, specifically:

[0097] ① Weigh the raw materials by weight, including 50 parts of halloysite nanotubes, 125 parts of 30% acetic acid, and 600 parts of deionized water;

[0098] ② 50 parts of halloysite nanotubes and 125 parts of 30% acetic acid were reacted in a water bath at 80°C for 2 hours, fully stirred at a speed of 1000 rpm and then allowed to stand for 24 hours. After standing, the acid-leached halloysite nanotubes were washed with 600 parts of deionized water, the washing supernatant was filtered off, and the operation was repeated until neutral;

[0099] ③ Dry the washed halloysite nanotubes at 80°C for 6 hours and grind them into powder. Put the washed halloysite nanotubes into a muffle furnace and heat them at 450°C for 3 hours to dry them, and finally obtain a flue gas suppressant.

[0100] Comparative Example 2

[0101] The preparation method of the smoke suppressant of this comparative example is basically the same as that of Example 3, except that only the inner cavity and surface of the halloysite nanotubes are surface modified, specifically:

[0102] ① Weigh the raw materials by weight, including 50 parts of halloysite nanotubes, 0.3 parts of stearic acid, and 0.3 parts of KH550 silane coupling agent;

[0103] ② Stir and blend 0.3 parts of stearic acid and 0.3 parts of KH550 silane coupling agent to obtain experimental intermediate C;

[0104] ③ Mix 50 parts of halloysite nanotubes and experimental intermediate C in a water bath, stir evenly, heat to 80°C, condense under reflux, and vacuum dry to obtain solution D;

[0105] ④ The solution D obtained in step ③ was centrifuged at 12000 rpm for 5 min. After centrifugation, it was dried at 150° C. for 12 h to finally obtain a smoke suppressant.

[0106] Comparative Example 3

[0107] The preparation method of the smoke suppressant of this comparative example is basically the same as that of Example 3, except that only iron ions are introduced into the inner cavity of the halloysite nanotubes, specifically:

[0108] ① Weigh the raw materials by weight, including 50 parts of halloysite nanotubes, 550 parts of ethanol solution, and 0.1 parts of anhydrous ferric chloride solution;

[0109] ② Mix 550 parts of ethanol solution containing 50 parts of halloysite nanotubes with 0.1 parts of anhydrous ferric chloride solution, filter and vacuum dry to obtain a smoke suppressant.

[0110] Performance Test The smoke and gas suppression effects of the smoke suppressants prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested, and commercially available halloysite nanotubes (blank control) without any treatment were introduced to test the smoke suppression effects.

[0111] The smoke suppression effect of asphalt at 160°C is shown in Table 1, and the asphalt type is 70# base asphalt.

[0112] Table 1 Smoke and gas suppression effect test of Examples 1 to 4, Comparative Examples 1 to 3, and blank control

[0113]

[0114]

[0115] From the results in Table 1, it can be seen that the smoke suppressants of Examples 1 to 4 prepared by the method of the present invention significantly reduce the emission of smoke and harmful gases generated during the construction process, wherein the smoke suppression rate is 32% to 39%, and the gas suppression rate is 70% to 75%, which is much greater than the smoke and gas suppression effects of Comparative Examples 1-3 and the blank control group. Among them, Comparative Examples 1-3 only treat the halloysite nanotubes under a single condition, and the blank control group does not perform any treatment on the halloysite nanotubes. It can be seen from the above data that the smoke suppressants prepared by the method of the present invention have a synergistic effect.

[0116] Example 5 This example is a method for preparing a smoke suppressant asphalt mixture, using AC-13 base asphalt and adding 5% smoke suppressant

[0117] A method for preparing a smoke suppression type asphalt mixture, the specific steps are:

[0118] S1. Weigh the raw materials by weight, heat 100 parts of base asphalt to 145°C, then add 5 parts of the prepared smoke suppressant to the base asphalt, stir at 4500 rpm for 1 hour, and then shear for 30 minutes to obtain smoke suppressant asphalt;

[0119] S2, 1956 parts of limestone crushed stone and 126 parts of limestone ore powder were placed in a 170°C oven and heated for 4 hours;

[0120] S3. Mix and stir evenly 1956 parts of heated limestone crushed stone, 126 parts of limestone mineral powder and the smoke suppression asphalt in S1 to obtain a smoke suppression asphalt mixture.

[0121] Performance test This application performs a performance test on the asphalt mixture prepared in Example 5

[0122] The smoke suppression asphalt and asphalt mixture prepared in the above examples were tested according to the standard JTG E20-2011 "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", and the test results are shown in Tables 2 and 3 below.

[0123] Table 2 Smoke suppression asphalt performance test results

[0124]

[0125] Table 3 Performance test results of smoke suppression asphalt mixture

[0126]

[0127] The invention relates to a smoke inhibitor and a preparation method thereof and application in asphalt, wherein a modification method of halloysite nanotubes has a simple process and low cost, and impurities on the surface and inner cavity of the halloysite nanotubes are removed by acid washing and roasting, and iron ions are introduced into the inner cavity of the halloysite nanotubes, so that the smoke adsorption effect of the halloysite nanotubes reaches an optimal state; as shown in Table 1, the smoke inhibitor of the invention can significantly reduce the emission of smoke and harmful gases generated during the construction process, wherein the smoke suppression rate is 32% to 39%, and the gas suppression rate is 70% to 75%, greatly improving the air quality of the construction environment; as shown in Tables 2 and 3, the high temperature stability, low temperature crack resistance and water stability of the smoke suppression type asphalt mixture all meet the "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004), and at the same time, it has a better smoke suppression effect and is suitable for large-scale application and production.

[0128] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments. On the basis of the present invention, some modifications or improvements can be made thereto, which is obvious to those skilled in the art. Therefore, these modifications or improvements made on the basis of not departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for preparing a smoke suppressant, characterized in that: The following steps are included: 1) Weigh the components by weight: 10-50 parts of halloysite nanotubes, 25-125 parts of acid solution, 0.1-2.5 parts of anhydrous ferric chloride, 500-600 parts of deionized water, 500-600 parts of ethanol, 0.3-1.5 parts of silane coupling agent, and 0.3-1.5 parts of stearic acid; 2) washing the halloysite nanotubes with acid and then washing with water until they are neutral; 3) drying, grinding and calcining the washed halloysite nanotubes to obtain intermediate A; 4) Dissolving intermediate A in an ethanol solution, mixing with anhydrous ferric chloride, and drying to obtain intermediate B; 5) mixing a silane coupling agent and stearic acid to obtain an intermediate C; 6) Intermediate B and intermediate C are mixed, condensed and refluxed, and then dried to obtain solution D; 7) The solution D is centrifuged and dried to obtain a smoke suppressant.

2. The preparation method according to claim 1, characterized in that: The silane coupling agent in step 1) is an aminosilane coupling agent.

3. The preparation method according to claim 1, characterized in that: The acid solution in step 1) is dilute sulfuric acid or dilute acetic acid.

4. The preparation method according to claim 3, characterized in that: The concentration of the acid solution in step 1) is 30-40%.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The index of the halloysite nanotubes in step 1) is 30-50 nm, and the specific surface area is 30-70 m 2 / g, length 100~500nm, mesh number 1250~2000mesh.

6. The preparation method according to claim 1, characterized in that: The acid washing method in step 2) is to mix the halloysite nanotubes with an acid solution and react them in a water bath at 75 to 85° C. for 1.5 to 2.5 hours.

7. The preparation method according to claim 6, characterized in that: The drying conditions in step 3) are drying at 75-85° C. for 5-7 hours, and the calcination conditions are calcining at 400-500° C. for 3-5 hours.

8. The preparation method according to claim 6 or 7, characterized in that: The centrifugation condition in step 7) is centrifugation at a rotation speed of 12000-14000 rpm for 5-10 min, and the drying condition is drying at 120-180° C. for 10-15 h.

9. A smoke suppressant prepared according to the method of any one of claims 1 to 8.

10. A smoke suppressant asphalt containing the smoke suppressant according to claim 9, characterized in that: The smoke suppressant asphalt can be obtained by uniformly mixing the smoke suppressant with the heated asphalt, wherein the smoke suppressant accounts for 1% to 5% of the mass of the asphalt.

Citation Information

Patent Citations

  • A smokeless soluble rubber powder composite modified asphalt and preparation method thereof

    CN118085595B